Letter to the Editor: The Role of D-Dimers in the Initial Evaluation of COVID-19 [Letter] - Patel S (Dove Medical Press, 2022)
Sachin Patel Emergency Department, Stoke Mandeville Hospital, Buckinghamshire Healthcare NHS Trust, Aylesbury, UKCorrespondence: Sachin Patel, Emergency Department, Stoke Mandeville Hospital, Buckinghamshire Healthcare NHS Trust, Aylesbury, UK, Email sachin.patel23@nhs.net View the original paper by Dr Baroiu and colleagues